STRATEGI PEDAGANG KAKI LIMA (PKL) DALAM MEMPERTAHANKAN USAHA PADA MASA PANDEMI COVID-19 (Studi Kasus PKL di Kawasan Tugu Kota Selong) - Muhamad Raju Pangestu; Baiq Rizka Milania Ulfah (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2023)
This research is entitled " THE STRATEGIES OF STREET TRADERS (PKL) IN SUSTAINING BUSINESS DURING THE COVID-19 PANDEMIC (Case Study of PKL in the Tugu City Selong Area)". In this study, researchers wanted to find out how the conditions of the street vendors around Taman Tugu Selong were during the Covid-19 pandemic and what strategies had to be taken to maintain business during the Covid 19 pandemic based on SWOT analysis. The type of this research is qualitative research with a descriptive approach to the SWOT analysis method. The results of this study are. During the Covid 19 pandemic, many traders did not sell at Taman Tugu Selong as a result of the implementation of the PSBB (Large-Scale Social Restrictions). Whereas based on the SWOT analysis the strategy that must be carried out in maintaining a business is a WO strategy by seeking to improve promotion strategies so as to increase demand for goods sold and try to promote using online media so that when unexpected conditions such as low visitors can be minimized by online marketing system.